“EVERYBODY CAN BE A HERO”: KAJIAN REPRESENTASI PAHLAWAN DALAM IKLAN TELEVISI M-150: “EVERYBODY CAN BE A HERO”: KAJIAN REPRESENTASI PAHLAWAN DALAM IKLAN TELEVISI M-150 - Permana, Rangga; Suzan, Nessa (Jurnal Kajian Budaya dan Humaniora, 2023)
Commercials on television play a role in displaying the symbols that make up the meaning of "hero." The concept of advertising is formulated so as to increase product sales from a business perspective. The effectiveness of verbal and nonverbal techniques is maximized. Advertising has entered a modern signification order in which messages are designed to subtly influence the audience's attitudes, cognitions, and lifestyle behaviors in order to satisfy their deepest desires or aspirations through product consumption and alter their perceptions of the reality portrayed in the advertisement. The development of the hero concept in this advertisement is inextricable from the creator's interaction with the researched object, the consumer in this instance. As a consequence of this interaction, almost all television advertisements, including the advertisement for the "Everyone Can Be a Hero" version of the M-150, use new connotations to increase their commercial appeal. This study seeks to determine, through the construction of signs, the representation that forms the meaning of the hero in the M-150 television advertisement version of Everybody Can Be a Hero. Charles Sanders Peirce's semiotic analysis was therefore conducted using a qualitative research method. The results demonstrate that the hero is portrayed not only through physical strength, but also through inner fortitude. This is supported by the signals that compose it, which stem from the product's concept and positioning. 15 icon signs, 20 index signs, 5 symbols, and multiple uses of video techniques containing aspects of the hero depict the hero's significance. The language of film is the use of video techniques, which includes camera angles, lighting arrangements, and the use of sound or audio.